1994
DOI: 10.1111/j.1399-302x.1994.tb00286.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of binding of fibrinogen to each bacterium on coaggregation between Porphymmonas gingivalis and Streptococcus oralis

Abstract: Fibrinogen inhibits the coaggregation between Porphyromonas gingivalis and Streptococcus oralis. In this study, we determined which bacterium interacts with fibrinogen in this inhibitory process. Although preincubation of each bacterium with fibrinogen did not inhibit coaggregation, its activity was completely eliminated by the addition of protease inhibitors such as N-ethylmaleimide (NEM), p-chloromercuriphenyl sulfonate and N alpha-p-tosyl-L-lysine chloromethyl ketone to the preincubation mixture with fibrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…A number of salivary components are capable of interacting with P. gingivalis. 14 Several components such as fibrinogen, 15 histatins, 16 and fibronectin 17 can inhibit bacterial adherence. On the other hand, salivary proline-rich proteins (PRPs)/proline-rich glycoproteins (PRGs) and statherin were found to act as salivary receptors for the organism as well as several other plaque-forming bacteria.…”
Section: In the Oral Cavitymentioning
confidence: 99%
“…A number of salivary components are capable of interacting with P. gingivalis. 14 Several components such as fibrinogen, 15 histatins, 16 and fibronectin 17 can inhibit bacterial adherence. On the other hand, salivary proline-rich proteins (PRPs)/proline-rich glycoproteins (PRGs) and statherin were found to act as salivary receptors for the organism as well as several other plaque-forming bacteria.…”
Section: In the Oral Cavitymentioning
confidence: 99%
“…Molecules present in these fluids that are bound by bacteria have the potential to modulate co-adherence. Salivary molecules including lysozyme and histatins, together with serum molecules such as fibrinogen, can inhibit adhesion of S. mitis, S. oralis, or S. crista to P. gingivalis (Murakami et al, 1991;Nagata et al, 1994). Hence, these molecules may comprise part of a host defense mechanism against colonization by P. gingivalis.…”
Section: Streptococcal Adhesion To Other Cellsmentioning
confidence: 99%
“…S chenkein & G enco (37) demonstrated that components in plasma show a resemblance to those in crevicular fluid. Plasma has been shown to intensively inhibit coaggregation between P. gingivalis and S. mitis or S. oralis (14, 29). Thus, the effect of plasma on individual interaction among bacterial species tested was investigated.…”
Section: Discussionmentioning
confidence: 99%
“…N agata et al. (14) showed that fibrinogen and/or its fragments mask the sites on P. gingivalis cells that are responsible for coaggregation with S. oralis . It is therefore considered that fibrinogen is one of the most potent inhibitors for interactions among bacterial species tested.…”
Section: Discussionmentioning
confidence: 99%